How is COVID-19 changing the ways doctors make end-of-life decisions?. Issue 12 (25th July 2022) - Chang, Benjamin Kah Wai; Matthews, Pia
Abstract : Background: This research explores how the COVID-19 pandemic has changed the ways doctors make end-of-life decisions, particularly around Do Not Attempt Cardio-Pulmonary Resuscitation (DNACPR), treatment escalation and doctors' views on the legalisation of euthanasia and physician-assisted suicide. Methods: The research was conducted between May and August 2021, during which COVID-19 hospital cases were relatively low and pressures on NHS resources were near normal levels. Data were collected via online survey sent to doctors of all levels and specialties, who have worked in the NHS during the pandemic. Results: 231 participants completed the survey. The research found that over half of participants reported making more patients DNACPR than prepandemic, and this was due, at least in part, to an increased focus on factors including patient age, Clinical Frailty Scores and resource limitations. In addition, a sizeable minority of participants reported that they now had a higher threshold for escalating patients to ITU and a lower threshold for palliating patients, with many attributing these changes to formative experiences gained during the pandemic. Finally, our study found that there has not been a statistically significant change in the views of clinicians on the legalisation of euthanasia or physician-assisted suicide since the start of the pandemic. Conclusion: The COVID-19 pandemic appears to have altered several aspects of end-of-life decision making, and many of these changes have remained even as COVID-19 hospital cases have declined.